ANALYSIS OF THE IMPACT OF MONEY SUPPLY, FOREIGN DEBT, INTEREST RATES, AND BANK CREDIT ON INFLATION IN INDONESIA (2022–2024) - Dina Septiani; Nia Angelia; Lina Kurniati (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the impact of the money supply, foreign debt, interest rates, and bank credit on inflation in Indonesia during the period 2022–2024. Inflation is a crucial indicator in maintaining macroeconomic stability because its dynamics are influenced by both monetary and external factors. A quantitative approach using the causal associative method is applied in this study. Secondary data in the form of monthly time series were used, comprising a total of 36 observations sourced from the Badan Pusat Statistik and Bank Indonesia. The Ordinary Least Squares (OLS) multiple linear regression analysis method was used, accompanied by the HAC Newey West standard error correction to address heteroscedasticity and autocorrelation. The research results indicate that, partially, the money supply has a positive effect, though not statistically significant, on inflation. Meanwhile, foreign debt exhibits a significant negative effect on inflation, indicating that an increase in external debt during the study period is associated with a decline in inflation through financing support and macroeconomic stability. Interest rates and bank credit each have a positive but statistically insignificant effect on inflation. Simultaneously, all four independent variables were found to have a significant effect on inflation. These findings suggest that Indonesia’s inflation during the 2022–2024 period was influenced by a combination of monetary and financial factors acting in concert.